Enterprise Integration with Biogas for Quality of Life: A Case of Nepal - Yadav, Maheshwar Prasad (Journal of Advanced Academic Research, 2015)
This paper aims at examining the integration of enterprise with biogas that contributes for quality of life in Nepal. The results have been estimated by using the data of FY 1992/93 to 2010/11. The number of biogas plants, cultural development, health and sanitation, reduction of greenhouse gas emission, forest conservation, and production of compost fertilizer has been comprised as variables for this study. Among others, Leslie Alvin White's model has been employed in this study. White introduced a formula, P = ET; Where, E is a measure of energy consumed per capita per year, T is the measure of efficiency in utilizing energy harnessed, and P represents the degree of cultural development in terms of product produced. The study establishes a significant role of enterprise integration with biogas for quality of life. It improves health and sanitation through providing clean energy and smokeless kitchen that directly associated with children and women's health and environment. The results shows improvement in people’s livelihood through starting agro & forest based micro enterprises by utilizing saved time due to biogas installation. Likewise, the study reveals that 415,314 tons of compost fertilizer can be produced annually that can promote agro-based enterprises. Moreover, 2.4 tons of reduction in greenhouse gas emission annually per household can be achieved by new Clean Development Mechanism (CDM) methodology. Last but not least, 296,653 trees can be protected per year that enhance greenery and protect environment. As a whole, all these factors contribute for enterprise integration in one way or another that play a vital role for the quality of life.Journal of Advanced Academic Research Vol.1(1) 2014: 68-75